Studies in Monetary Economics - Schupp, Fabian; Justus Liebig University Giessen (My University, 2020)
Since the outbreak of the great financial crisis (GFC) in 2008 and later also in response to the consequences of the sovereign debt crisis, central banks around the globe have not only reacted by rapidly cutting the key policy rates to zero or even negative levels, but have also adopted a series of unconventional monetary policy measures. In the euro area, many of these measures, in particular those in immediate response to the GFC and the sovereign debt crisis were primarily aimed at repairing an impaired monetary policy transmission process. While the ECB was successful in this regard, a persistently subdued inflation outlook over the medium term and rising deflationary pressures led the ECB to deploy a set of unconventional policy measures to increase the accommodative stance of monetary policy. These comprised targeted longer-term refinancing operations and purchases of sovereign bonds, alongside private sector assets, such as asset-backed securities, covered bonds and corporate bonds.Naturally, the increased breadth of the monetary policy tool kit also led to an increasing complexity of monetary policy analysis. However, central banks depend on reliable information about the effectiveness of their measures in order to take appropriate decisions about its future monetary policy course. In this regard, given the importance of interest rates in the monetary transmission process and the evaluation of the monetary stance, the analysis of the term structure of risk free interest rates plays a key role, and had to evolve significantly over the last years. For the analysis of the term structure of interest rates, term structure models have long been an established and widely used tool among central bankers. Yet, with interest rates close to their effective lower bound (ELB) and central banks no longer targeting only the very short end of the yield curve, the demands on these models have increased substantially. This is especially true for the euro area, where analysis is impeded by a relatively short sample of interest rates in light of their high persistence, and a lower bound that kept changing over the course of the past years. Against this backdrop, Chapters 1 and 2 of this thesis propose modelling advances that allow to deepen the understanding of the yield curve and its drivers and improve upon existing approaches of modelling the term structure of interest rates. In particular, Chapter 1 - "With a little help from my friends: survey-based derivation of euro area short rate expectations at the effective lower bound", joint work with Felix Geiger - discusses the particularities of the euro area yield curve and how these can best be addressed within a shadow rate term structure model (SRTSM) framework. The Chapter introduces a SRTSM for the euro area OIS yield curve which explicitly accounts for the relatively short euro area sample and the high persistence in interest rates, fulfilling two important criteria, i.e. (i) a good model fit and (ii) plausible short- and long-term rate expectations that can be used for policy analysis. We find that given the severe small sample problem with a protracted period of low interest rates near the time-varying ELB, a shadow short rate model specification that incorporates actual as well as expected changes of the ELB is important from a statistical and economic point of view. Moreover, incorporating survey forecasts on short- and long-term interest rate expectations, improves the model´s capability to pin down the future path of short rates, which is particularly important when decomposing longer-term yields and forward rates.Furthermore, the proposed model generates expected short rate paths that do not violate lower bound restrictions. The most likely path of the short rate follows a trajectory which is in line with survey forecasts and which is consistent with the intended policy rate path of the ECB´s Governing Council as implied by its forward guidance. As this forward guidance links the possible lift-off of policy rates to the end of net asset purchases of the extended asset purchase programme (APP), changes in the expected duration of net asset purchases should translate into changes of the most likely short rate path. Our model results are in line with this hypothesis and highlight the announcement of asset purchases as a commitment device for future short rates.In addition, we estimate the impact of monetary policy shocks on the forward curve and its components based on a high frequency external instrument approach. To do so, we employ predictive regressions of the factor innovations on selected monetary policy instruments which allows us to model the reaction of the forward curve in a non-linear way. This allows us to identify both conventional and unconventional monetary policy shocks. In consequence, our model produces a U-shaped response of the forward curve in response to a conventional monetary policy shock, which emphasizes the shock´s communication/forward guidance character. In contrast, the median reaction to an unconventional monetary policy shock is negative at the long end and spills over to medium-term maturities. The largest impact of an unconventional monetary policy shock on the forward curve stems from the forward premium and takes place at the 10-year maturity horizon pointing to the transmission of non-standard measures via duration extraction. At medium-term maturities our model attributes a more prominent role to the expectations component. Finally, in the run-up to the start of asset purchases in March 2015 unconventional monetary policy shocks considerably contributed to the drop in long-term interest rates according to our model. Term premia as well as short rate expectations fell in response to these monetary policy shocks thereby also highlighting the signaling channel of non-standard monetary policy measures.While Chapter 1 focuses on the nominal term structure of euro area OIS yields, one needs to bare in mind that by definition, any move in nominal rates is driven by either the inflation component or a change in real rates. While central banks aim to steer the level and expectations of nominal rates, it is essential for monetary authorities to effectively influence real rates in the intended manner, as according to economic theory it is the level of real rates that matters for consumption and investment and thus ultimately drives inflation.Therefore, Chapter 2 - "The (ir)relevance of the nominal lower bound for real yield curve analysis" - presents a joint model for euro area nominal rates and inflation-linked swap (ILS) rates, which allows isolating real and inflation components of nominal interest rates. Different from earlier models focusing on the euro area (see Hördahl and Tristani, 2014 and García and Werner, 2012), the model in this thesis comprises the ELB of nominal interest rates as a new and unique feature for this class of models. As has been argued before, failing to do so may otherwise lead to implausible estimates for rate expectations and premia and consequently also to a non-reliable inference of the dynamics of inflation expectations and real rates embedded in observed nominal rates (Carriero, Mouabbi and Vangelista, 2018).Indeed, results suggest that modelling the ELB is of relevance for two reasons. First, an analysis of responses by yield components to shocks to the inflation factor shows that the magnitude and sign of these responses are conditional on the degree to which the ELB is binding. For nominal yields, we observe a decreasing impact of inflation shocks across all maturities, the closer rates are to the ELB. The response of real rates is non-linear. While nominal rates are distant from the ELB, real rates show a positive response to a positive inflation shock; they react negatively when nominal rates are close to or at the ELB. Overall, these results suggest that the ELB introduces non-linearities with a meaningful impact on structural relationships in the economy. The finding of non-linear or time-varying impulse responses relates to findings of Mertens and Williams (2018) who, in a small structural model, find that the lower bound alters the distributions of both interest rates and inflation by restricting the central bank´s scope for action. The findings further relate to work by King (2019) and Geiger and Schupp (2018) who likewise attest a decreasing effectiveness of conventional monetary policy at the ELB due to a receding reactiveness of interest rates, in particular, at shorter maturities.Second, isolated changes in the ELB impact, in particular, nominal and real forward rates mainly through their expectations component. In our analysis, a 10-bp cut in the ELB yields an average impact of -5 (-3) bps on 24-month (120-month) nominal forward rates. These impacts are almost entirely transmitted through real rate expectations and only to a very small extent through real or inflation risk premia. Thus, these results imply that the central bank can lower real rate expectations by solely changing the effective lower bound of interest rates. These results build upon work of Lemke and Vladu (2016) who have shown that the perceived lower bound by itself can be considered a monetary policy tool to lower yields across all horizons.As much as the GFC and the following sovereign debt crisis led to a permanent change in the Eurosystem´s monetary framework, it was followed by an equally large change in financial regulation. Among the main causes of the financial crisis had been liquidity shortages in the global financial sector as banks failed to prepare themselves for short-term liquidity stress. In response, the Basel Committee on Banking Supervision introduced the Liquidity Coverage Ratio (LCR), which obliges banks to ensure a sufficient amount of unencumbered highly liquid assets to withstand a 30 day liquidity stress scenario. In addition, the newly introduced Net Stable Funding Ration (NSFR) demands that banks procure sufficient stable funding over a time horizon of one year.While a full assessment of the effectiveness of the newly introduced regulations is challenging at this stage, Chapter 3 - "The role of structural funding for stability in the German Banking Sector", joint work with Leonid Silbermann - presents an empirical evaluation of the relevance of stable funding for the probability of banks experiencing financial distress. The objective of this analysis is to provide an empirical assessment of the effectiveness of funding regulation introduced in response to the GFC as to this end financial theory has not been conclusive on this question. On the one hand, wholesale funding, especially owing to its short-term maturity structure, is often thought to have a disciplining effect on banks as it prompts them to rollover their debt frequently. Given their high expertise, wholesale investors would also be expected to provide better and closer monitoring of banks than depositors would, while also opening up more investment opportunities for banks (Brunnermeier, 2019, Calomiris and Kahn, 1991, Huang and Ratnovski, 2011).On the other hand, a sufficiently high degree of wholesale funders´ seniority might force otherwise financially sound banks into inefficient liquidation given publicly available but imprecise information like market prices and credit ratings. Using a noisy negative public signal on banks´ project quality, wholesale investors have the incentive to reduce their monitoring and withdraw their funds if their seniority governing the division of banks´ liquidation value is sufficiently high. This holds true especially for large and publicly traded banks, while traditional banks holding opaque and non-tradable loans should still profit from wholesale funding and its disciplining character. A higher share of deposit funding (along with a higher precision of the public signal) might even fortify this mechanism, given that more deposits incentivize early withdrawals by wholesale creditors, as they raise the liquidation value (Huang and Ratnovski, 2011).Another potential source of instability of wholesale funding are the so called liquidity spirals (Brunnermeier and Pedersen, 2009). The reason is that a major part of wholesale funding is obtained by borrowing against assets subject to haircuts. Operating at the edge of being equity constrained, these haircuts determine a bank´s maximum leverage, so that rising haircuts force banks to either raise more equity or deleverage by selling off assets in order to hold their leverage constant. If there is a general increase in haircuts due to rising volatility in the market, the banking system might experience extreme funding stress.Against this background, Chapter 3 presents empirical evidence based on supervisory data on critical events of financial institutions spanning a time period of 19 years, which is combined with balance sheet data as well as other supervisory data in order to estimate the effect of stable funding on banks´ probabilities of financial distress. Due to the fact that the NSFR cannot be calculated exactly for the time period prior to its implementation, we use the loan-to-deposit ratio and the loan-to-interbank-liabilities ratio as proxies for stable funding. Indeed, our results suggest that stable funding makes critical events significantly less likely for savings banks and credit cooperatives, suggesting a stabilizing effect of the net stable funding ratio.
Keywords: ddc:330